Disaster Education as a Strategy for Managing Flood Risk in Rural Communities: A Case Study of Trawasan Village - Wachidatullailiya, Meitha; Putra, Ahmad Lufianto Eka; Qomari, Ilham Nurul; Putri, Saskia Aulia; Eduat, Stephanus Maria (Jurnal Penelitian Geografi, 2025)
Flooding is one of the most frequent natural disasters in Indonesia, particularly in Trawasan Village, Jombang Regency, where low topography and inadequate drainage systems exacerbate the risk. This study aims to evaluate community understanding of flood hazards and the effectiveness of disaster education in enhancing preparedness. A descriptive qualitative design with a Grounded Theory approach was employed, using unstructured interviews, direct observations, and document analysis as data collection methods. The findings reveal that community preparedness remains low, largely due to insufficient education and limited awareness of evacuation procedures. The study emphasizes the urgent need to strengthen disaster education programs to build resilience and reduce vulnerability. Furthermore, the results underscore the critical role of collaboration between government institutions and local communities in implementing effective disaster risk reduction strategies. Enhancing such cooperation is essential to improve safety, minimize disaster impacts, and promote sustainable community well-being in flood-prone areas.